(untitled) (Huellas, 2018)
Territorial divisions of labor coexistin the cities; these can be thought of as circuits of urban economy. Such circuits differ according to their degrees of organization, use of technology and capital. When these degrees are high we can clearly recognize an upper circuit constituted by banks, commerce and modern industries. In dialectical opposition, the lower circuit of urban economy is composed of labor-intensive activities with a low level of capitalization and technology. In the fishing activity of Mar del Plata we can recognize circuits of urban economy. Despite being the same branch of economic activity, the actors involved have different forms of organization and use of capital. This also implies a certain form of relationship with the financial variable. Through a productive territorial specialization such as fishing, the aim of this work is to understand the way in which the actors, who are diverse, participate in the work, producing and consuming, according to their possibilities of organization, uses of technology and capital and the way in which finances expand the linkages and create other dependency links. Fishing companies of the upper circuit are analyzed and two aspects that characterize this circuit are considered: the productive innovations and the access to banked money. Other possible forms of organization and financing of the so-called "yellow boats" linked to the lower circuit of fishing activity are also examined.